Violência no trânsito "À Moda Brasileira": insegurança, letalidade e impunidade - Russo, Maurício Bastos (2012)
The Brazilian car fleet almost doubled its size in the last decade. At the same time, the number of victims from car accidents rises every year. This thesis aims at understanding how economic and cultural conditions contribute to violence caused by cars. In spite of the fact that this is a common issue in every country nowadays, in some cases, such as it happens in Brazil, the problem is not the total number of car accidents but their lethal percentage. In Brazil, contrary to what is seen in developed countries, most automobiles, a kind of vehicle most frequently involved in accidents with victims, do not offer basic safety equipment, such as airbags and anti-lock braking system (ABS) which are major deterrent of fatalities. One should add to this the state’s inability to regulate properly the social environment created for vehicles. Exemption from punishment for violators, ranging from light infractions, such as parking at unauthorized places, to more serious ones, such as homicides fired by car accidents foments illegal practices. Problems involving training of new drivers and issuing of a driver’s license release thousands of unauthorized drivers to take Brazilian streets and roads. The country’s economic development did not create an equal process of transformation that allowed drivers to changing into individuals capable of respecting alterity involving other users of the transit system. Transit is still a privileged space for some who do not respect the existing social hierarchy and who defy those who consider driving a car an exercise of democracy.